Alur Kerja Tahap Produksi Karakter Animasi Serial 3D Menggunakan Perangkat Lunak Maxon Cinema 4D - Ardiyan, Ardiyan (Bina Nusantara University, 2011)
3D Animation serial for television needs have been showed in the national television program, especially fantasy theme and educational program for children. There are so many and sequential needs which tricked by instant and high quality production so the work flow in creating 3D animation serial are facilitating the producers. The article will explain specifically how the software of Maxon Cinema 4D in process production in 3D animation serial. The article will also clarify and focus on how the work flow of Maxon Cinema 4D software in processing production and post-production stages. The writer does research including audio visual tutorial, end-result comparison and rendering time between some software, self-observation of work flow in creating 3D animation serial using Maxon Cinema 4D software and digital literature study (e-book).